Sensory and Emotional Perception of Wooden Surfaces through Fingertip Touch - Bhatta, Shiv R.; Tiippana, Kaisa; Vahtikari, Katja; Hughes, Mark; Kyttä, Marketta (Frontiers in Psychology, 2017)
Previous studies on tactile experiences have investigated a wide range of material surfaces across various skin sites of the human body in self-touch or other touch modes. Here, we investigate whether the sensory and emotional aspects of touch are related when evaluating wooden surfaces using fingertips in the absence of other sensory modalities. Twenty participants evaluated eight different pine and oak wood surfaces, using sensory and emotional touch descriptors, through the lateral motion of active fingertip exploration. The data showed that natural and smooth wood surfaces were perceived more positively in emotional touch than coated surfaces. We highlight the importance of preserving the naturalness of the surface texture in the process of wood-surface treatment so as to improve positive touch experiences, as well as avoid negative ones. We argue that the results may offer possibilities in the design of wood-based interior products with a view to improving consumer touch experiences.